2020
DOI: 10.1002/adma.202004630
|View full text |Cite
|
Sign up to set email alerts
|

Precise Control of Perovskite Crystallization Kinetics via Sequential A‐Site Doping

Abstract: film deposition process to achieve desired morphology and microstructure. [2-6] Most of the high-efficiency PSCs were produced by either one-step or two-step fabrication methods. The very first MAPbI 3-based PSC was fabricated via a one-step spincoating process developed by Kojima et al. in 2009. [7] However, the one-step fabricated perovskite film typically exhibited a dendritic morphology with poor coverage. To address the morphology issue, a two-step spin-coating process was developed by Xiao et al. [8] and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
122
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(122 citation statements)
references
References 69 publications
(72 reference statements)
0
122
0
Order By: Relevance
“…Reproduced with permission. [50] Copyright 2020, Wiley-VCH. g) Activation energies of the αand δ-phase of FAPbI 3 in the dependence of OH − concentration.…”
Section: Xrd Characterization Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [50] Copyright 2020, Wiley-VCH. g) Activation energies of the αand δ-phase of FAPbI 3 in the dependence of OH − concentration.…”
Section: Xrd Characterization Methodsmentioning
confidence: 99%
“…By adopting DFT simulation, Qin et al revealed that the incorporation of GA + into CsPbI 3 is not only beneficial for promoting the phase transition from δ-CsPbI 3 to the perovskite α-phase, but also favorable for eliminating pinholes via Ostwald ripening and inhibiting grain boundary migration (Figure 1f). [50] Chen et al simulated that a low OH − concentration will make δ-phase FAPbI 3 a much higher activation energy of 5.352 eV compared to the α-phase FAPbI 3 (3.518 eV), which is favorable for the fabrication of pure α-phase FAPbI 3 (Figure 1g). [51] With the increasing of OH − concentration, the activation energies of δ-phase FAPbI 3 will decrease from 5.352 to 4.143 eV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their low cost and high power conversion efficiencies, lead halide perovskite solar cells (PSCs) have become promising technology for future clean energy harvesting. [1][2][3][4][5][6] Currently, the most popular PSCs are planar ones, in which the active perovskite film is sandwiched between an electron transport layer (ETL) and hole transport layer (HTL). In the standard architecture of the planar PSCs (ITO/ETL/perovskite/HTL/Au), the most widely used HTL (ETL) is Spiro-OMeTAD (SnO 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, researchers utilize interface engineering, solvent engineering, crystalline engineering, additive engineering, composition engineering, and so on to improve efficiency and stability, and prevent lead leakage by adsorption and/or encapsulation with organic compounds. [ 13–22 ]…”
Section: Introductionmentioning
confidence: 99%